Comparative Evaluation of Allergodiagnostic of Tuberculosis in Children - I. V. Mikheeva; E. Yu. Burdova; A. A. Melnikova (Эпидемиология и вакцинопрофилактика)
The comparative analysis of results of the tuberculin skin test (TST) and of the skin test with the recombinant tuberculosis allergen (Diaskintest - DST) in 7978 children with active tuberculosis revealed for the first time in 2013 - 2014 was carried out. The negative DST result and positive TST result are observed at 551 (6.91%) of patients. 92 patients (1.15%) had negative both tests, and at 98 people (1.23%) DST has yielded positive result, PM - negative. Other patients had positive both tests. In general, by means of DST tuberculosis initially hasn't been revealed at 643 (8.06%) patients, and by means of TST - at 190 (2.38%) patients. The difference is statistically reliable (t = 9.16; P < 0.05). Dynamics of tests results at patients with active tuberculosis was studied. The result of DST remained negative for a year in18.7% of patients, in 26,7% of patients with initially negative DST the result became positive in 3 months, in 2.7% - a year after the first testing. Tuberculosis of various forms and localizations, including TB+, was diagnosed for children with initially negative results of DST and positive TST.